KEADILAN DALAM PERPEKSTIF AL-QUR’AN - Agustami, Eli (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2019)
Allah provides information on justice through the Qur’ran which is the meaning as and explained in Surah al-Infihtar verse 7. It could be meant fairness or balanced that indicates the perfect human beings are structured based on principles of balance. In other words, the balance or justice is an aspect in human dimension that should be embedded in his or her life. the Qur'an also provides several meanings related to justice, which come from the root word 'adl and means something that is true, an attitude that is not impartial, safeguarding one's rights and the right way to make a decision, and understanding that is directly related to the side of justice. The teachings of Islam through the Qur'an and Hadith have principles and laws in safeguarding and enforcing justice, because the truth is absolute and absolute justice is the justice that comes from God the Almighty and the just. In a state that carries out its authority fairly, it will be able to perpetuate its power, but oppositely, if its power is carried out unfairly which is the justice only applied to the weak community, its power will only wait for the time of its destruction.